Ethical Acceptability of Neuromarketing : Relevance, Limits and Limitations - Sultana, Nazia; Nangunoori, Ram (Prabandhan: Indian Journal of Management, 2008)
Applying the methods of the neurology lab to the questions of business world has become a common phenomenon. In this paper, we try to relate the application of neuroscience to the field of marketing/advertising and examine its ethical acceptability, relevance, limits and limitations. We believe that an understanding of the neuro-scientific changes that influence the positive buying behaviour is not going to be of much use to marketing field itself. It only studies the neurological pattern that is impacting the buying behaviour but this pattern needs to be generated in the mind of the buyer by means of conventional/traditional marketing. Use of neuroscience technologies to boost advertising effectiveness or attain tangible marketing objectives may prove to be a potential danger to the consumer’s autonomy and choice in deciding upon a positive buying behaviour. One can argue that the purpose of all marketing initiatives is to manipulate consumer behaviour yet it is an attack on the autonomy and private thought. Adding to the existing threats, neuroscientists are busy exploring possible solutions with intrusive technology to decipher a person’s mental movements. The basic idea of this paper is to highlight that the neurological process that takes place internal to an individual can neither be ethically manipulated nor freely influenced without regulatory constraints. In this paper we also bring out our theory called "sweet-ball theory" to explain that neurological techniques are irrelevant to the activity of marketing. Hence, we strongly believe that an extensive study of neurological sciences in the field of marketing is a futile exercise.